The Effects of Zoledronate on the Structure, Dissolution and Bioactivity of the Bioglass Composite: An Investigation by MAS-NMR and ICP-OES Methods - Xuan Vuong, Bui (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4DO - 10.25073/2588-1140/vnunst.4826, 2018)
Abstract: Composite of bioglass (BG) with 0.1 wt.% of zoledronate (Z) has been elaborated for medical applications as reported in a previous study [1]. The synthetic material has been proven to be bioactive. This study used two physical-chemical methods: MAS-NMR (Magic angle spinning – nuclear magnetic resonance) and ICP-OES (Inductively coupled plasma – optical emission spectrometry) to clarify the effect of zoledronate on the structure, dissolution and bioactivity of BG. The obtained results show that the use of 0.1 wt.% of zoledronate modified the structural network, slowed down the dissolution and stimulated the bioactivity of bioglass. Keywords: Bioglass, zoledronate, composite, lyophilization, in vitro, bioactivity. References [1] X.V. Bui, H. Oudadesse, Y. Le Gal, A. Mostafa, P.Pellen and G. Cathelineau, Chemical Reactivity of Biocomposite Glass-Zoledronate, Journal of the Australian Ceramic Society, 46 (2010) 24. [2] D.F. Williams, Definitions in Biomaterials, Consensus Conference for the European Society for Biomaterials, Chester, UK, 1986. [3] L.L. Hench, Bioceramics: From Concept to Clinic, Journal of the American Ceramic Society, 74 (1991) 1487. [4] L.L. Hench, The story of Bioglass, Journal of Materials Science: Materials in Medicine, 17 (2006) 967. [5] H. Fleisch, A. Russell, R.G.G. Bisaz, S. Muhlbauer and D.A. Williams, The inhibitory effect of phosphonates on the formation of calcium phosphate crystals in vitro and on aortic and kidney calcification in vivo, European Journal of Clinical Investigation, 1 (1970) 12. [6] H. Fleisch, R.G.G. Russell and M.D. Francis, Diphosphonates inhibit formation of calcium phosphate crystals in vitro and pathological calcification in vivo, Science, 165 (1996) 1262. [7] R.G.G. Russell, R.C. Muhlbauer, S. Bisaz, D.A. Williams and H. Fleisch, The influence of pyrophosphate, condensed phosphates, phosphonates and other phosphate compounds on the dissolution of hydroxyapatite in vitro and on bone resorption induced by parathyroid hormone in tissue culture and in thyroparathyroidectomised rats, Calcified Tissue, 6 (1970) 183. [8] F.P. Coxon, K. Thompson, M.J. Rogers, Recent advances in understanding the mechanism of action of bisphosphonates, Current Opinion in Pharmacology, 6 (2006) 307. [9] C.T. Leu, E. Luegmayr, LP. Freedman, G.A. Rodan, A.A. Reszka, Relative binding affinities of bisphosphonates for human bone and relationship to antiresorptive efficacy, Bone, 38 (2006) 628. [10] G.H. Nancollas, R. Tang, R.J. Phipps, Z. Henneman, S. Gulde, W. Wu, Novel insights into actions of bisphosphonates on bone - differences in interactions with hydroxyapatite, Bone, 38 (2006) 617. [11] S.E. Papapoulos, Bisphosphonate actions - physical chemistry revisited, Bone, 38 (2006), 613. [12] M.J. Rogers, J.C. Frith, S.P. Luckman, F.P. Coxon, H.L. Benford, J. Monkkonen, S. Auriola, K.M. Chilton and R.G.G. Russell, Molecular Mechanisms of Action of Bisphosphonates, Bone, 24 (1999) 73. [13] M.F. Moreau, C. Guillet, P. Massin, S. Chevalier, H. Gascan, M.F. Basle, D. Chappard, Comparative effects of five bisphosphonates on apoptosis of macrophage cells in vitro, Biochemical pharmacology, 73 (2007) 718. [14] J.R. Berenson, L.S. Rosen, A. Howell, L. Porter, R.E. Coleman, W. Morley, R. Dreicer, S.A. Kuross, A. Lipton, J.J. Seaman, Zoledronic acid reduces skeletal-related events, Cancer, 91 (2001) 1191. [15] J.R. Berenson, R. Vescio, K. Henick, C. Nishikubo, M. Rettig, R.A. Swift, F. Conde, J.M. Von Teichert, A phase I, open label, dose ranging trial of intravenous bolus zoledronic acid, a novel bisphosphonate, in cancer patients with metastatic bone disease, Cancer, 91 (2001) 144. [16] T. Kokubo, H. Kushitani, C. Ohtsuki, S. Sakka, T. Yamamuro, Effects of ions dissolved from bioactive glass-ceramic on the surface apatite formed, Journal of Materials Science: Materials in Medicine, 4 (1993) 1. [17] D. Massiot, F. Fayon, M. Capron, I. King, S. Le Calvé, B. Alonso, J. O. Durand, B. Bujoli, Z. Gan and G. Hoaston, Modelling one and two dimensional solid state NMR spectra, Magnetic Resonance in Chemistry, 40 (2002) 70. [18] G. Engelhardt, D. Michel, High-resolution solid state NMR of silicates and zeolites, Wiley Book Publisher, 1987. [19] M. W. G. Lockyer, D. Holland, R. Dupree, NMR investigation of the structure of some bioactive glasses, Journal of Non-Crystalline, 188 (1995) 207. [20] I. Elgayar, A. E. Aliev, A. R. Boccaccini, R. G. Hill, Structural analysis of bioactive glasses, Journal of Non-Crystalline, 351 (2005) 173. [21] A. Angelopoulou, V. Montouillout, D. Massiot, G. Kordas, Study of the alkaline environment in mixed alkali compositions by multiple-quantum magic angle nuclear magnetic resonance (MQ-MAS NMR), Journal of Non-Crystalline, 354 (2008) 333. [22] S. Josse and all, Novel biomaterials for bisphosphonate delivery, Biomaterials 26 (2005) 2073. [23] H. Roussière and all, Reaction of Zoledronate with β-Tricalcium Phosphate for the Design of Potential Drug Device Combined Systems, Chemistry of materials 20 (2008) 182.